Resection of retroperitoneal tumors with inferior vena cava involvement without caval reconstruction. Issue 7 (9th August 2022) - Palacios, Arnold R.; Schmeusser, Benjamin N.; Midenberg, Eric; Patil, Dattatraya; Xie, Lillian; Nabavizadeh, Reza; Ogan, Kenneth; Cardona, Kenneth; Maithel, Shishir K.; Master, Viraj A.
Abstract: Background and Objectives: Retroperitoneal tumors with involvement of the inferior vena cava (IVC) often require resection of the IVC to achieve complete tumor removal. This study evaluates the safety and efficacy of IVC ligation without caval reconstruction. Methods: A retrospective chart review of patients who underwent IVC ligation (IVC‐Ligation) and IVC resection with reconstruction (IVC‐Reconstruction) at our institution between May 2004 and April 2021 was performed. Outcomes from the two surgical techniques were compared via univariate analysis using the Kruskal–Wallis test for continuous variables and Fisher's exact test for categorical variables. Results: Forty‐nine IVC‐Ligation and six IVC‐Reconstruction surgeries were identified. There were no differences in baseline demographics, tumor characteristics, complication rates, postoperative morbidity, or overall 5‐year survival between groups. IVC‐Reconstruction patients were more likely to require intensive care unit admission (83% vs. 33%; p = 0.0257) and the IVC‐Ligation cohort had a tendency to present with nondebilitating postoperative lymphedema (35% vs. 0%; p = 0.1615), which resolved for most patients. Conclusions: IVC‐Ligation is a viable surgical option for select patients presenting with retroperitoneal tumors with IVC involvement and provides acceptable short‐ and medium‐term outcomes.